The First Fatal Intoxication with 3-MeO-PCP in the UK and a Review of the Literature. Issue 5 (5th March 2022) - Copeland, Caroline S; Hudson, Simon; Treble, Ric; Hamnett, Hilary J
Abstract: The phencyclidine derivative 3-methoxyphencyclidine (3-MeO-PCP) is a potent dissociative hallucinogen. Sought for recreational use as a novel psychoactive substance, it can also induce acute psychological agitation and pathophysiological cardiorespiratory effects. Due to the harms associated with its use, 3-MeO-PCP was added to the "Green List" of materials covered by the 1971 Convention on Psychotropic Substances as a Schedule II substance by the United Nations Commission on Narcotic Drugs in April 2021. There have been 15 previous reports of fatal intoxications following 3-MeO-PCP use, but only one was attributable to 3-MeO-PCP intoxication alone. In this report, we detail the first fatality due to 3-MeO-PCP intoxication to be reported in the UK, along with a review of the surrounding literature. While the blood concentrations associated with 3-MeO-PCP toxicity and fatality remain unclear, by providing details of sample collection and storage conditions, this case will aid in future interpretations. Furthermore, this case suggests that 3-MeO-PCP toxicity may be exacerbated by exercise. Users of 3-MeO-PCP should be cautioned against its use as a "club drug" or in a similar setting where elevations in heart rate, body temperature and blood pressure may occur.